Voltage controlled dual-wavelength ZnO/Au/MgZnO UV photodetectors. (July 2018) - Hu, Nan; Jiang, Dayong; Zhang, Guoyu; Guo, Zexuan; Zhang, Wei; Yang, Xiaojiang; Gao, Shang; Zheng, Tao; Liang, Qingcheng; Hou, Jianhua
Graphical abstract: Highlights: A dual-wavelength UV photodetector has been constructed with a sandwich structure. The ratio of the two response peaks can be changed by changing the bias voltage. The principle was investigated by interpretation of the depletion widths. Abstract: In this work, dual-wavelength UV photodetectors were successfully constructed by growing ZnO and MgZnO layers on SiO2 substrates with ZnO/Au/MgZnO structure. The photodetectors exhibited high performance and the influence of different thickness of MgZnO layers was investigated. Moreover, simply by adjusting the applied voltage on the devices, the ratio of the two response peaks (caused by MgZnO and ZnO layers) changed therewith. The detecting properties may originate from the two layers having different increasing rates where the existence of Schottky junctions plays an important role. The photodetectors are meaningful for fabricating dual-wavelength optoelectronic devices for practical applications.